Systematic Literature Review: Application of Andragogy Principles in Makeup Training in Non-Formal Education - Fransisca Devyyana Putri Astari; Imam Shofwan (Jurnal Penelitian Pendidikan, 2026)
Face makeup training is an important component of non-formal education that focuses on developing vocational skills, enhancing independence, and supporting economic empowerment, particularly for adult learners. Given the characteristics of adult participants who are self-directed, experience-based, and problem-oriented the application of andragogical principles is essential in designing effective training programs. This study aims to examine the implementation of andragogical principles in face makeup training within non-formal education through a Systematic Literature Review (SLR) combined with bibliometric analysis using VOSviewer. Literature was collected from publications published between 2015 and 2025 through Google Scholar and screened using predefined inclusion, exclusion, and quality assessment criteria. The selected studies were analyzed to identify publication trends, keyword co-occurrence patterns, dominant research themes, and methodological approaches. The VOSviewer analysis reveals that research on andragogy in face makeup training clusters around experiential learning, practice-oriented instruction, skill development, and adult empowerment. The findings indicate that the consistent application of andragological principles contributes positively to learner engagement, mastery of makeup skills, self-confidence, and readiness for employment or entrepreneurship. Methodologically, most studies employ descriptive qualitative and quantitative approaches, using instruments such as observation, interviews, and questionnaires. Overall, this review highlights the importance of integrating andragogical principles into face makeup training programs as a strategic approach to improving the quality and relevance of adult learning in non-formal education.